Lamyat Ibn Al-Wardi: A Guiding Principle for Effective Public Administration and Peacebuilding - Isiaka Adewale Lawal; Jamiu Adebayo Azeez (PT. Student Rihlah Indonesia, 2026)
This paper is an examination of the timeless wisdom contained in Ibn Wardi’s 14th century poem on public administration and peacebuilding. Through a critical analysis of Lāmiyat Wardi’s odes, the paper explores Lāmiyat’s guiding principles, emphasizing moral virtues, compassion, and knowledge pursuit in public administration to resonate with contemporary challenges. This paper, through a careful analysis from an Islamic lens, uncovers a framework for effective public administration, highlighting transparency, accountability, and responsiveness with a view to finding solutions to the lingering challenges in modern public administration and peacebuilding, by stressing the enduring relevance of the contributions of Arabo-Islam scholars in fostering an inclusive, stable, and peaceful society.